Education policy: explaining, framing and forming. Issue 3 (3rd May 2016) - Adams, Paul
Abstract : This paper presents a new heuristic device for the analysis of educational policy. Through an examination of the Evaluative State and the work of Brian Fay, the paper considers the way in which educational policy is subject to rational and linear forms of policy action and implementation. To counter this, positioning theory is deployed to consider the way in which we are produced both by discourse and the language of the 'moment' in discursive acts. Using the work of Gee, the paper contends that policy texts and policy Discourse 'themselves form policy, that is, they position policy-explanation and policy-framing within the bounds of the institution and so give policy form'. Problematically, such mechanisms may succumb to the 'death of subject' and accordingly I offer a third method by which we might conceive of education policy: the discursively produced position call. Subsequently, I propose a tri-partite theory for the examination and understanding of policy: policy-explaining, the production of policy texts; policy-framing, the ways in which all can be positioned by texts and Discourse to produce the meanings imbued upon policy; and, policy-forming, the impact of moment-by-moment conversational acts for their production of the policy text itself, that is, the ways in which policy is locally formed rather than locally mediated .